Introduction - D'Ippoliti, Carlo (PSL Quarterly Review, 2015)
The short editorial introduces to the new issue of the Review. Starting from the 2015 volume, the journal is changing its copyright policy as well as its open access policy. Curiously often, economists consider everyone susceptible to respond to incentives, except the economists themselves. On the contrary, as shown for example by Necker (2014), “scientific misconduct” is very much diffused in economics, with e.g. almost one in five economists refraining from citing works in low-ranking journals, more than half (51.9%) admitting of not always checking the contents of the works they cite, and lower but equally alarming percentages of economists admitting of copying and plagiarising or massaging the data and faking empirical results. Therefore, while in some cases it may amount to little more than lip service, restating basic rules of ethics seems all the more relevant within the discipline of economics, and the present editorial wishes to lay down the minimum requirements of ethical behaviour expected from authors, editors, and referees. JEL codes: Y20, A11, A12